FUNGSI MANAJEMEN DALAM PEMBINAAN KINERJA KARYAWAN BANK PEMBIAYAAN RAKYAT SYARIAH (BPRS) BANDAR LAMPUNG - Mubasit; Rouf Tamim; Badarudin (Jurnal At Taajir, 2020)
This study aims to describe the function of management in fostering employee performance at the Islamic People's Funding Bank (BPRS) Bandar Lampung. This research is a descriptive research with a qualitative approach. The subject of this research is the structural officer of the Islamic People's Financing Bank (BPRS) Bandar Lampung. Data collection techniques using interviews, observation, and scrutiny of documents. The validity of the data was tested by triangulation of sources. The data were analyzed with the stages of organizing data, reducing data, grouping by category, displaying data, and drawing conclusions. Performance appraisal at the Bandar Lampung Syariah People's Financing Bank is carried out every three months which is accumulated once a year. With the performance appraisal process Identify goals such as about salary increases and promotions. After that, the boss determines the tasks that are carried out in his work for subordinates. Furthermore, superiors check the tasks carried out by their employees and provide performance appraisals to employees and finally discuss the results of the assessment with employees. The performance assessment at the Bandar Lampung Syariah People's Financing Bank is carried out by the direct supervisor, without involving external parties. The Bandar Lampung Islamic People's Financing Bank uses a past-oriented performance appraisal method with a rating scale technique. The performance appraisal of the Islamic People's Financing Bank is based on the elements of the assessment, namely: honesty, discipline, work performance, cooperation, skills, loyalty, leadership, and communicativeness. The performance assessment at the Bandar Lampung Sharia People's Financing Bank is carried out once a year, using a draft form that is already available at the Bandar Lampung Sharia People's Financing Bank. The performance appraisal is used for all employees, unless there are additional fields such as marketing, Teller, and Customer Service. Performance appraisal for marketing is by looking at the achievement of the target in one month, the target goes up or down for its achievement. As for Tellers and Customer Service, namely with proficiency in delivering to customers